Relationship Between Crown-to-Root Angulation of Maxillary Central Incisor and Lower Lip Line In Different Malocclusions: Crown-to-Root Angulation of Maxillary Central Incisor - Khan, Sameera Jamshed Ali; Awaisi, Zubair Hassan; Ahmed, Zubair (Pakistan Journal of Health Sciences, 2023)
Collum angle, supplementary angle between longitudinal axis of crown-to-root, is an important consideration in patients receiving orthodontic treatment This angulation in labio-lingual direction is a key factor for proper occlusion and is greatly affected by lower lip line levels in different malocclusions. Objective: To find the relationship between collum angle of maxillary central incisor and lower lip line in patients presenting with different malocclusions. Methods: Cross-sectional, Comparative Study conducted in Orthodontics department of Nishtar Institute of Dentistry, Multan.From September 2020 to February 2021. Lateral cephalometric radiographs of 105 patients (39 males and 66 females)were selected with age range of 9-30 years. Patients were divided in 4 groups i.e Class I, Class II div I, Class II div II and class III. Collum angle was measured along with assessing lower lip-line level with central incisor. One-way ANOVA test was applied to compare level of lower lip and collum angle. Results: Mean value of collum angle was 5.82˚±5˚ for class I, 3.68˚ ± 9˚ for class II div I, 11.7˚± 5˚ for class II div II, and 6.88˚± 7 ˚for class III. Collum angle of maxillary central incisor was greatly increased in patients with class II div II malocclusion than other groups. Conclusions: Collum angle found to be highest in class II div II malocclusion group. Lower lip line resting on middle third level of maxillary central incisor crown in div II group explains this exceeding value of collum angle